\(\displaystyle \sqrt{a}\left(3-\sqrt{ab}\right)=\)
Умножим каждое слагаемое в скобках на \(\displaystyle \sqrt{ a}{\small . } \) Тогда:
\(\displaystyle \sqrt{a}\left(3-\sqrt{ab}\right)= \color{blue}{ \sqrt{a}}(3-\sqrt{ab})= \color{blue}{ \sqrt{ a}}\cdot 3- \color{blue}{ \sqrt{ a}}\cdot \sqrt{ ab} {\small . }\)
Перемножая и учитывая, что \(\displaystyle \sqrt{ ab} =\sqrt{a}\sqrt{b}{\small , }\) получаем:
\(\displaystyle \sqrt{ a}\cdot 3- \sqrt{ a}\cdot \sqrt{ ab}= 3\sqrt{ a}- \sqrt{ a}\sqrt{a}\sqrt{b}{\small . }\)
Так как \(\displaystyle \left(\sqrt{ a}\right)^2=a{\small ,}\) то
\(\displaystyle 3\sqrt{ a}- \sqrt{ a}\sqrt{a}\sqrt{b}=3\sqrt{ a}- \left(\sqrt{ a}\right)^2\sqrt{b}=3\sqrt{ a}-a\sqrt{ b} {\small . }\)
Таким образом,
\(\displaystyle \sqrt{a}\left(3-\sqrt{ab}\right)=3\sqrt{ a}-a\sqrt{ b} {\small . }\)
Ответ: \(\displaystyle 3\sqrt{ a}-a\sqrt{ b}{\small . } \)